Is there an association between early childhood caries and serum iron and serum ferritin levels? - Mostafa Sadeghi; Reza Darakhshan; Ali Bagherian (Wolters Kluwer Medknow Publications, 2012)
Background: Early childhood caries (ECC) is a virulent form of dental caries that can destroy the primary dentition of preschool children. The purpose of this study was to investigate a possible association between ECC with serum iron and serum ferritin levels. Materials and Methods: Following the ethical approval, 204 children aged 24-71 months were recruited for a double-blind, randomized cross-sectional study. Each child was examined clinically for dental caries using the World Health Organization criteria in Rafsanjan, Iran. Decayed, extracted, and filled primary teeth (deft) index was used to measure the dental caries. To determine serum iron and serum ferritin levels 2 mL blood was collected from each child. Data were then analyzed by Pearson's correlation coefficient and t-test using SPSS-16.0 software. Results: The mean values and their standard deviations of the deft index and levels of serum iron and ferritin were 2.4(± 3.3), 93.8(± 29.0) μg/dL and 63.1(± 32.2) ng/mL, respectively, with the two latter within. There was no significant difference between genders. Pearson's correlation coefficient showed that there was a statistically significant inverse association between ECC and serum iron level (P<0.05); but no association was found with the serum ferritin level. Conclusion: The deft index decreased significantly with increasing serum iron levels, but there was no association between ECC experience and serum ferritin levels.